2015
DOI: 10.5114/ceji.2015.51358
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Archaea prevalence in inflamed pulp tissues

Abstract: Archaea have been detected in several ecological niches of the human body such as the large intestine, skin, vagina as well as the oral cavity. At present, archaea are recognized as nonpathogenic microorganisms. However, some data indicate that they may be involved in the etiopathogenesis of several diseases, including intestinal diseases as well as oral diseases: periodontitis, peri-implantitis and endodontitis. In this study, on the basis of 16S rRNA gene sequence analysis, we examined whether archaea might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
2
22
0
3
Order By: Relevance
“…DNA from root canals of one of these patients showed also the presence of ‘red complex bacteria’ (Holt and Ebersole 2005). These results confirm the presence of archaea in root canals and provide additional insights into the polymicrobial communities in endodontic infections associated with clinical symptoms (Mansfield et al 2012; Efenberger et al 2015). Among this group of ‘red complex bacteria’ is also Tannerella forsythia , whose glycosylated S-layer proteins TfsA and TfsB have been characterised recently (Posch et al 2011) ( vide supra and Fig.…”
Section: Archaeal Surface Appendagessupporting
confidence: 75%
“…DNA from root canals of one of these patients showed also the presence of ‘red complex bacteria’ (Holt and Ebersole 2005). These results confirm the presence of archaea in root canals and provide additional insights into the polymicrobial communities in endodontic infections associated with clinical symptoms (Mansfield et al 2012; Efenberger et al 2015). Among this group of ‘red complex bacteria’ is also Tannerella forsythia , whose glycosylated S-layer proteins TfsA and TfsB have been characterised recently (Posch et al 2011) ( vide supra and Fig.…”
Section: Archaeal Surface Appendagessupporting
confidence: 75%
“…Members of the Archaea also colonize the oral cavity, especially within subgingival plaques and on tooth surfaces [ 21 , 36 38 ], while the diversity seems to be very narrow. We detected archaeal sequences in 73.0% of tongue samples, but only 16.9% of subgingival pocket samples.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that archaeal crude extracts induce the recruitment of CD4 + and CD19 + cells in the lung along with a strong production of serum IgG (Blais-Lecours et al 2011). Importantly, human endogenous viable methanogens species are associated with oral diseases (Lepp et al 2004;Vianna et al 2006Vianna et al , 2008Vianna et al , 2009Vickerman et al 2007;Jiang et al 2009;Efenberger et al 2015), intestinal diseases (Scanlan et al 2008;Lee et al 2013;Blais-Lecours et al 2014;Mira-Pascual et al 2015) and obesity (Zhang et al 2009;Mbakwa et al 2015). Methanogens activate human peripheral blood cells to release the important immune mediator TNF (Blais-Lecours et al 2014), and methanogen-specific IgGs are detectable in periodontic and inflammatory bowel disease (IBD) patients, documenting their potential as activators of the human immune system in environments where the strict methanogen conditions allow their survival.…”
Section: Introductionmentioning
confidence: 77%